A National Asset: 50 Years of the Strategic and Defence Studies Centre - Ball, Desmond; Carr, Andrew (ANU Press, 2016)
This volume commemorates the 50th anniversary of the Strategic and Defence Studies Centre (SDSC). The Centre is Australia's largest body of scholars dedicated to the analysis of the use of armed force in its political context and one of the earliest generation of post-World War II research institutions on strategic affairs. The book features chapters replete with stories of university politics, internal SDSC activities, cooperation among people with different social and political values, and conflicts between others, as well as the Centre's public achievements. It also details the evolution of strategic studies in Australia and the contribution of academia and defence intellectuals to national defence policy.